Anaerobic digestion of pineapple waste using a microbial consortium - Ab. Aziz, Siti Norshidah (2019)
Anaerobic digestion of the agro-industrial pineapple waste has great potential to generate biogas, an alternative energy resource to compensate the deprivation of global fossil fuel over the years. The objectives of this study were to identify and characterize a microbial consortium (MC) from Palm Mill Oil Effluent (POME) as well as preliminarily evaluate its potential as a biogas producer through pineapple waste anaerobic digestion. The MC was subjected to gram and methylene blue staining techniques, Dinitrosalicylic Acid (DNS) method, 16S rRNA and Internal Transcribed Spacer (ITS) sequencing, and phylogenetic tree analysis. Next, gas production from the anaerobic digestion was analyzed by water displacement and Residual Gas Analyzer (RGA). Based on the phenotypic and genotypic identification, the MC was comprised of four bacteria, including Bacillus cereus, Acinetobacter radioresistens, Klebsiella sp., and Stenotrophomonas maltophilia, as well as a fungus Aspergillus fumigatus. The A.radioresistens strain in this study was found to be a novel facultative anaerobe strain with the potential of producing biogas. Higher overall cellulase activity of the MC was found in contrast to the amylase activity during the pineapple waste digestion process. The water displacement method showed potential gas production of 287±135 cm3, comprising of 80.15% nitrogen, 16.94% oxygen, 2.63% water vapours, 0.19% carbon dioxide, 0.08% hydrogen sulphide and 0.01% hydrogen. In conclusion, this study had successfully identified and characterized the MC as well as determined its potential in biogas production, although the gas analysis showed an absence of the desired biogas, methane which could be acquired through further optimization of the biodigestion process.